Surgical natural uveoscleral outflow activation and phacoemulsification with intraocular lens implantation in the combined treatment of patients with glaucoma and cataract combination - Zavgorodnaya, N. G.; Gaidarzhi, T. P. (Zaporozhye Medical Journal, 2014)
Aim. Surgery of glaucoma in combination with cataract is an important modern ophthalmology issue. Combination of the diseases can be met in 17-76 % patients. Methods and results. To deal with the task in a most effective way we used a new kind of surgery by activating of a natural uveoscleral outflow with implantation of antiglaucomatous collagenous drain Xenoplast in combination with cataract phacoemulsification and implantation of intraocular lens in 15 patients (18 eyes). Statistically proved postoperative decline of ophthalmotonus and improvement of sight sharpness indexes comparing to preoperative data was established. Conclusion. That shows the combination of a proposed natural uveoscleral outflow surgical activation and cataract phacoemulsification to be an effective strategy at different stages of glaucomatous process and phacoscotasmus.